Faktor – Faktor Yang Mempengaruhi Pemerataan Pendapatan di Indonesia - Achmad Sidqiy; Syamsul Amar (Universitas Negeri Padang, 2020)
This research illustrates the influence of economic growth, domestic investment and government expenditure to distribution income in Indonesia with variables (1) GDP per capita, (2) Domestic Investment and (3) Goverment Expenditure. This research uses panel data from 2012-2017, which consist 32 province in Indonesia, by using a method linear regression and use Fixed Effect Model (FEM). the results obtained from this research is (1) Economic growth has a negative significant effect to inequality income in Indonesia. (2) Domestic investment has negative effect but not significant to inequality income in Indonesia. (3) Goverment expenditure has a positive and significant effect to inequality income in Indonesia